Low‐dose adjuvant dexmedetomidine did not decrease propofol sedation requirements in children undergoing gastrointestinal endoscopy. Issue 10 (23rd September 2022) - Johnson, Eric G.; Weaver, Sarah G.; Batt, Kelsey L.; Weaver, Robert H.; Schadler, Aric; Hall, Sarah J.
Abstract: Background: Propofol is the cornerstone of deep sedation during pediatric esophagogastroduodenoscopy (EGD), though adjuvant dexmedetomidine may provide propofol‐sparing benefits. Objective: The objective of the study was to evaluate whether adjuvant dexmedetomidine decreases the total propofol dose in pediatric patients undergoing EGD. Methods: This single‐center, retrospective, cohort study evaluated the total propofol dose in pediatric patients undergoing EGD with and without the use of adjuvant dexmedetomidine. Secondary outcomes included the change in hemodynamics across the perioperative continuum and post‐procedure recovery time. A multivariable general linear regression was performed to identify associated variables for recovery time post‐procedure. Results: A total of 159 patients were included in the study; 88 patients received dexmedetomidine and propofol (DEX‐PRO), and 71 patients received propofol only (PRO). The median [interquartile range (IQR)] propofol dose in the DEX‐PRO group was 0.26 [IQR, 0.17–0.36] mg kg −1  min −1 which was not significantly different than the PRO group at 0.27 [IQR, 0.21–0.34] mg kg −1  min −1, p  = 0.730. Evaluation of secondary end points showed the DEX‐PRO group had more cases of post‐anesthesia care unit (PACU) hypotension (61% vs. 34%, p  = 0.001) and a longer recovery time (32.9 ± 14.1 vs. 25.6 ± 10.8 min, p  < 0.001) versus the PRO group, respectively. Multivariable linear regression demonstrated that age and the use of dexmedetomidine were associated with prolonged recovery. Conclusion: Adjuvant dexmedetomidine did not reduce propofol requirements compared with propofol alone in pediatric patients undergoing EGD. More hypotension and a longer postoperative recovery time were also seen in patients receiving adjuvant dexmedetomidine for their endoscopic procedure.